1998
DOI: 10.1042/bj3300115
|View full text |Cite
|
Sign up to set email alerts
|

Harpin and hydrogen peroxide both initiate programmed cell death but have differential effects on defence gene expression in Arabidopsis suspension cultures

Abstract: Programmed cell death is increasingly viewed as a key component of the hypersensitive disease resistance response of plants. The generation of reactive oxygen species (ROS) such as H2O2 triggers a cell death programme in Arabidopsis suspension cultures following challenge with the bacterial elicitor harpin. Both harpin and exogenous H2O2 initiate a cell death pathway that requires gene expression, and also act as signalling molecules to induce the expression of plant defence genes encoding enzymes such as phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
216
0
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(237 citation statements)
references
References 56 publications
15
216
0
6
Order By: Relevance
“…This concentration and the two time points were chosen based on earlier studies (Desikan et al, 1998a(Desikan et al, , 2000. Arabidopsis cultures have a very high H 2 O 2 scavenging capacity (Desikan et al, 1998a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This concentration and the two time points were chosen based on earlier studies (Desikan et al, 1998a(Desikan et al, , 2000. Arabidopsis cultures have a very high H 2 O 2 scavenging capacity (Desikan et al, 1998a).…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O 2 also activates mitogen-activated protein kinases (MAPKs), conserved signaling kinases that modulate gene expression and transduce cellular responses to extracellular stimuli Grant et al, 2000;Kovtun et al, 2000;Samuel et al, 2000). Furthermore, several studies indicate that H 2 O 2 is a key factor mediating programmed cell death (PCD) in response to pathogens, elicitors, and hormones (Tenhaken et al, 1995;Levine et al, 1996;Desikan et al, 1998a;Mittler et al, 1999;Solomon et al, 1999;Bethke and Jones, 2001). In addition, two recent studies have shown that H 2 O 2 is synthesized in response to exogenous abscisic acid (ABA), and that H 2 O 2 mediates, at least in part, ABA responses including stomatal closure and gene expression (Guan et al, 2000;Pei et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In some plant models, H 2 O 2 induces PCD (Desikan et al 1998, Houot et al 2001, Ren et al 2002, Gechev and Hille 2005 and in others it appears not to be required (Glazener et al 1996, Dorey et al 1999, Sasabe et al 2000, Ichinose et al 2001. Moreover, in H 2 O 2 -dependent PCD, PCD is only observed when the H 2 O 2 concentration reaches a threshold value as a result of a complex sequence of events including H 2 O 2 perception, suppression of H 2 O 2 scavengers (de Pinto et al 2002), activation of a MAPK signalling cascade (Ren et al 2002) and the co-ordinated regulation of at least 150 genes shown to be involved in controlling H 2 O 2 homeostasis (Mittler et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Our data appeared that lower levels of pulp browning correlated fairly well with the PAL activity, which confirms the conclusion that EBR has protective effects against pulp browning in eggplant fruit s during cold storage. It has been reported that hydrogen peroxide can induce the expression of PAL (Desikan et al 1998). Lin et al (2005) suggested that inhibiting the production of hydrogen peroxide by dimethylthiourea can decrease the PAL activity in rice cells.…”
Section: Pulp Browningmentioning
confidence: 99%